2014
DOI: 10.1111/efp.12137
|View full text |Cite
|
Sign up to set email alerts
|

First report on the association of Pestalotiopsis mangiferae with leaf blight disease of Canthium dicoccum in India

Abstract: The multi-use tree Canthium dicoccum (Rubiaceae) growing in shrub forests of Mysore, Mandya and Chamarajanagar (India) was severely affected by a leaf blight disease. The ascomycete Pestalotiopsis mangiferae was consistently isolated from symptomatic leaves and identified by micromorphology and ITS rDNA sequencing analysis. Pathogenicity test was performed and Koch's postulates were fulfilled. This is the first report of P. mangiferae causing leaf blight of C. dicoccum in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…The incidence at the field level (% tree infected) was not evaluated, but 70% to 100% have been reported in Italy [ 16 ]. Similar results have been reported for grey leaf spot disease with premature defoliation by pestalotiopsis-like fungi in other hosts, like Jatropha curcas , Canthium dicoccum , Vigna unguiculata , Cocos nucifera and Vacciniea corymbosum [ 40 , 41 , 42 , 43 , 44 ]. However, premature defoliation associated with grey leaf spot disease was not observed in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…The incidence at the field level (% tree infected) was not evaluated, but 70% to 100% have been reported in Italy [ 16 ]. Similar results have been reported for grey leaf spot disease with premature defoliation by pestalotiopsis-like fungi in other hosts, like Jatropha curcas , Canthium dicoccum , Vigna unguiculata , Cocos nucifera and Vacciniea corymbosum [ 40 , 41 , 42 , 43 , 44 ]. However, premature defoliation associated with grey leaf spot disease was not observed in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…It had evident that Pestalotiopsis caused minor diseases on mango and guava trees in Sri Lanka. However, many research reports revealed that Pestalotiopsis were causing widespread damage to some hardy trees like Rhododendron, conifers, Eucalyptus and Canthium dicoccumin trees in some countries (Hopkins and McQuilken , 2000;Mahadevakumar and Janardhana, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Koch’s postulates were performed to confirm the organismal association with the disease, and healthy leaves were inoculated with the conidial/spore suspension of N. vitis (10 6 conidia per ml) of the isolated fungal pathogen (isolate N. vitis MZ03) on 30 leaves by detached leaf assay method by following the protocols of Mahadevakumar and Janardhana (2014) and Mahadevakumar et al . (2018).…”
Section: Methodsmentioning
confidence: 99%